Nominal Interest Rate Pegging Under Alternative Expectations Hypotheses. (IMF Working Papers; Working Paper, 1988)
Nominal interest rate pegging leads to instability in an IS-LM model with a vertical long-run Phillips curve and backward-looking inflation expectations. However, it does not lead to instability in several large multicountry econometric models, apparently primarily because these models have nonvertical long-run Phillips curves. Nominal interest rate pegging leads to price level and output indeterminacy in a model with staggered contracts and rational expectations. However, when a class of money supply rules with interest rate smoothing is introduced, and interest rate pegging is viewed as the limit of interest rate smoothing, the price level and output are determinate.